Early-life experience and stress resilience - Ng, Yan Ling (2015)
Stress is an inherent part of life and depressive disorders often manifests at a young age. While many studies have linked early-life stress to morphological deficits in the medial prefrontal cortex (mPFC) neurons, much less is known about the roles of its prelimbic (PrL) neurons to stress resilience. In this project, we compared the effects of maternal separation (MS) and environmental enrichment (EE) on the dendritic morphology of PrL neurons and examined if EE can aid to recover the structural impairment evoked by MS in Wistar rats. Morphological characteristics of PrL neurons were studied and analysed by Golgi-staining and Sholl analysis. The results show that although there were no statistically significant changes in the dendritic length (DL) and branch points (BP) in MS and EE alone, a statistically significant interaction between MS and EE was noted in DL by two-way ANOVA, where DL was significantly lower in MS-STD and AFR-EE compared to AFR. These findings suggest, opposite to literature findings, that EE does not help recover MS-impaired PrL neurons. Future research could be done to understand the recovery rate of PrL neurons throughout development to gain further insight on the remodeling dynamics of PrL neurons, thereby conferring stress resilience.